Variance Aware Secure Routing for Heterogeneous Wireless Sensor Networks - Kumar, Kamal; Verma, A. K.; Patel, R.B. (Malaysian Journal of Computer Science, 2013)
Secure Communication is important parameter in unattended and hostile environment. Wireless Sensor Networks (WSNs) are deployed and operate in vulnerabilities and are candidate networks which should be commissioned for security provisioning in end to end communications. Because of their specialized applications many solutions in terms of cryptographic, Intrusion Detection and Key Management have been proposed. Most solutions lack and seem of ignoring the fact that route is as strong as weakest link in the route with respect to other links in the route. Variance of number of keys and high average number of keys on routes is an issue that we tried to resolve in our proposal using non-uniform key pre-distribution in Heterogeneous Wireless Sensor Networks (HWSNs). Analytical and Simulation based study supports our concern and reports an improvement in Average number of keys in almost 60 percent routes and decreasing variance in almost 50 percent routes in random and probabilistic neighbourhood.